Gene Cloning, Expression and Characterization of a Novel Xylanase from the Marine Bacterium, Glaciecola mesophila KMM241 - Bai-Cheng Zhou (Marine Drugs, 2013)
Marine xylanases are rather less studied compared to terrestrial xylanases. In this study, a new xylanase gene, xynB, was cloned from the marine bacterium, Glaciecola mesophila KMM241, and expressed in Escherichia coli. xynB encodes a multi-domain xylanase XynB of glycoside hydrolase (GH) family 8. The recombinant XynB comprises an N-terminal domain (NTD) with unknown function and a catalytic domain, which is structurally novel among the characterized xylanases of GH family 8. XynB has the highest identity (38%) to rXyn8 among the characterized xylanases. The recombinant XynB showed maximal activity at pH 6–7 and 35 °C. It is thermolabile and salt-tolerant. XynB is an endo-xylanase that demands at least five sugar moieties for effective cleavage and to hydrolyze xylohexaose and xylopentaose into xylotetraose, xylotriose and xylobiose. NTD was expressed in Escherichia coli to analyze its function. The recombinant NTD exhibited a high binding ability to insoluble xylan and avicel and little binding ability to chitosan and chitin. Since the NTD shows no obvious homology to any known carbohydrate-binding module (CBM) sequence in public databases, XynB may contain a new type of CBM.